Effective therapeutic strategies in a preclinical mouse model of Charcot–Marie–Tooth disease. Issue 24 (19th July 2021) - Nuevo-Tapioles, Cristina; Santacatterina, Fulvio; Sánchez-Garrido, Brenda; de Arenas, Cristina Núñez; Robledo-Bérgamo, Adrián; Martínez-Valero, Paula; Cantarero, Lara; Pardo, Beatriz; Hoenicka, Janet; Murphy, Michael P; Satrústegui, Jorgina; Palau, Francesc; et al.
Abstract: Charcot–Marie–Tooth (CMT) disease is a neuropathy that lacks effective therapy. CMT patients show degeneration of peripheral nerves, leading to muscle weakness and loss of proprioception. Loss of mitochondrial oxidative phosphorylation proteins and enzymes of the antioxidant response accompany degeneration of nerves in skin biopsies of CMT patients. Herein, we followed a drug-repurposing approach to find drugs in a Food and Drug Administration-approved library that could prevent development of CMT disease in the Gdap1 -null mouse model. We found that the antibiotic florfenicol is a mitochondrial uncoupler that prevents the production of reactive oxygen species and activates respiration in human GDAP1 -knockdown neuroblastoma cells and in dorsal root ganglion neurons of Gdap1 -null mice. Treatment of CMT-affected Gdap1 -null mice with florfenicol has no beneficial effect in the course of the disease. However, administration of florfenicol, or the antioxidant MitoQ, to pre-symptomatic GDAP1 -null mice prevented weight gain and ameliorated the motor coordination deficiencies that developed in the Gdap1 -null mice. Interestingly, both florfenicol and MitoQ halted the decay in mitochondrial and redox proteins in sciatic nerves of Gdap1 -null mice, supporting that oxidative damage is implicated in the etiology of the neuropathy. These findings support the development of clinical trials for translation of these drugs for treatment of CMT patients. Graphical Abstract: